Polymer–assisted forge–rolling disaggregation of detonation nanodiamonds and onion–like carbon. (2nd February 2015) - Kanygin, M.A.; Sedelnikova, O.V.; Bulusheva, L.G.; Okotrub, A.V.
Nanodiamonds (NDs) produced in a detonation process are strongly aggregated, which hampers fully realising their properties at the nanoscale, particularly, in composites. Moreover, during annealing, the tightly bonded ND particles are transformed into the so–called onion–like carbon (OLC), where several carbon onions are coated by joint graphitic layers. Here, we demonstrate that NDs and OLC can be disaggregated using a polymer–assisted forge–rolling. The isolated diamond nanocrystals and carbon onions with a size of ∼5 nm typical for the primary particles are observed by high–resolution transmission electron microscopy in polystyrene films after repeated rolling. We suggest that forces acting on aggregates through a strongly stretched polymer matrix are able to break the chemical bonds between carbon particles. Measurements of permittivity indicate that homogeneous distribution of individualised carbon onions in polymers can significantly increase the shielding efficiency of a composite.